Evaluasi Program Inovasi Pelayanan Sistem Terpadu Pada Poli TBC - Asep Awaludin (Jurnal Ilmiah Wahana Pendidikan, 2021)
The purpose of this study was to describe the implementation of the integrated service system program at the TBC Poly. The object of research is the Ciwandan Health Center. The study used a qualitative method with a descriptive approach with data collection through structured interviews. From the results of the study, it can be concluded that 1) The implementation of the integrated service system program at the TB Polyclinic carried out by the Ciwandan Health Center on the input component is supported by implementing staff consisting of 6 officers and 2 cadres. The implementation of this system does not have a special budget at all because basically services for TB patients have been carried out at the Ciwandan Health Center. Integrated services at the TBC Polyclinic are carried out through 4 tables, namely the registration desk, examination desk, laboratory table and pharmacy desk. The results of the implementation of the integrated service system can be seen from the decrease in the rate of transmission of TB cases at the Ciwandan Health Center and the speed of patient recovery time, so that the doctor's examination activities become more effective on patients. TB patients and cadres gave positive responses regarding the quality of service from the integrated service system at the TBC Polyclinic at the Ciwandan Health Center.